Perspectives on accessibility in performance based on the analysis of Birita Procura-se" (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article presents an analysis of Birita Procura-se created by Ariadne Antico and Ésio Magalhães. Focusing on the perspective of accessibility, the study seeks to observe how the clown's performance, especially with the use of the flop, a specific clowning resource, favors the establishment of an accessible scene in which markers of disability are revisited through the displacement of the parameter of normality. As a methodological approach are used audio description (AD) and the questionnaire presented by Pavis in the book A análise de espetáculos (2003). The audio description is highlighted and exemplified once that it operates transversally in the study.
Keywords: performance analysis; accessible scene; clown; theater; accessibility